2014
DOI: 10.1007/s12263-014-0442-2
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-ethnic differences in genetic variants within the transmembrane protease, serine 6 (TMPRSS6) gene associated with iron status indicators: a systematic review with meta-analyses

Abstract: Transmembrane protease, serine 6 (TMPRSS6), is likely to be involved in iron metabolism through its pleiotropic effect on hepcidin concentrations. Recently, genome-wide association studies have identified common variants in the TMPRSS6 gene to be linked to anaemia and low iron status. To get a more precise evaluation of identified TMPRSS6 single nucleotide polymorphism associations with iron status in cohorts of differing continental ancestry, we conducted a systematic review with metaanalyses. We searched the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
2
25
0
2
Order By: Relevance
“…Genome Wide Association Studies, including a recent meta-analysis, indicate that TMPRSS6 genetic variants associate with red cell and iron traits in Caucasian and Asian populations. [21][22][23] The most common associated TMPRSS6 variant (rs855791, A736V) influences serum hepcidin levels. 24 The genetic susceptibility to iron deficiency is of special interest for transfusion medicine because it has implications for blood donation.…”
Section: Genetics and Iron Deficiencymentioning
confidence: 99%
“…Genome Wide Association Studies, including a recent meta-analysis, indicate that TMPRSS6 genetic variants associate with red cell and iron traits in Caucasian and Asian populations. [21][22][23] The most common associated TMPRSS6 variant (rs855791, A736V) influences serum hepcidin levels. 24 The genetic susceptibility to iron deficiency is of special interest for transfusion medicine because it has implications for blood donation.…”
Section: Genetics and Iron Deficiencymentioning
confidence: 99%
“…We identified three novel (p.Asp680Glufs*111; IVS13 1 1G>A; and p.Arg678Pro) and two already known [3,4] (p.Arg30Profs*31 and p.A621_Q624delAVAQ) TFR2 mutations associated with a juvenile-like clinical presentation in three young women (clinical, biochemical, and molecular data at diagnosis are summarized in Supporting Information Table S1). None of the probands had other known factors able to aggravate iron accumulation.…”
Section: Milenamentioning
confidence: 99%
“…Some studies have indicated that TMPRSS6 polymorphisms directly affect hepcidin transcription, while others have suggested that the polymorphisms may addictionally influence iron homeostasis by mechanisms independent of hepcidin expression. The latter theory could explain why rs855791 has not been found to be significantly associated with serum hepcidin in some studies [3].…”
mentioning
confidence: 97%
See 2 more Smart Citations